Les NTIC peuvent-elles transformer la vulgarisation agricole ? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
L'observatoire des NTIC du CTA, du 23 au 25 Septembre 2003